Rancang Bangun Sistem Informasi Pengelolaan Indikator Mutu dan Insiden Keselamatan Pasien di RSUD Temanggung - Yustin Yustin; Emilya Ully Artha; Ardhin Primadewi (JURIKOM (Jurnal Riset Komputer), 2021)
RSUD Temanggung has an important role and task in ensuring the continuity and quality of health services for the entire Temanggung residence. Hospital accreditation assessment is an effort to improve the quality of health services in hospitals. The Quality and Patient Safety Program (PMKP) is one of the accreditation committees at the RSUD Temanggung that handles hospital quality programs and patient safety incidents. To complete the quarterly work program made by the PMKP committee, data were collected in all units in the Temanggung Hospital. There is a need for a system to collect data in real-time so that the quality of health services at the RSUD Temanggung can be improved. The measured quality indicators are divided into 3 types, namely national quality indicators, priority quality indicators, and unit quality indicators. The system is built with 3 actors, namely admin, nurse, and director. The admin actor acts as a web manager on the access rights menu, the quality indicator menu, and the patient safety incident menu. The nurse actor acts as the manager of the quality indicator data. The director's role is to overview the graph of quality achievement in all units at the RSUD Temanggung. The results of system testing with beta testing instruments for admin actors (87%), nurse actors (88%), and director actors (94%) are based on several parameters to test the system's functionality according to each actor with a very feasible category. In addition to functionality testing, this system was also tested for performance, ease of searching for hospital quality/safety incident data, as well as ease of making and recapitulating quarterly reports by the PMKP committee with a success percentage of 95%.